Resonance Modeling and Control Via Magnetorheological Dampers - Letelier-Sotomayor, M; Stockle-Henriquez, J; Siginer, D (Birkhauser Verlag AG, 2016)
A method to model and minimize resonant structural oscillations using magnetorheological dampers is presented. The response of the magnetorheological fluid flowing in a circular tube under a pressure gradient to the applied variable magnetic field is tailored to determine the optimum stress field in the fluid to mitigate resonance effects. © 2016, Springer International Publishing.